Prognostic value of heart rate variability in atrial fibrillation recurrence following catheter ablation: A systematic review and meta-analysis - Zhang, Enyuan; Liang, Shuo; Sun, Tianhong; Xu, Jing; Lu, Fengmin; Wu, Dongyan; Zhang, Jingkun; He, Le; Zhang, Fan; Fan, Shaobo; Ma, Wei (Frontiers in Cardiovascular Medicine, 2023)
Background: Atrial fibrillation (AF) has been a worldwide health issue with increasing prevalence and mortality. Lately, increasing attention has been gained by the relationship between heart rate variability (HRV) and clinical prognosis of AF catheter ablation. We aimed to evaluate the prognostic value of HRV in AF recurrence. Methods: We searched systematically Web of Science, PubMed and Embase from inception until August 17th, 2022 to conduct the systematic review and meta-analysis. We included the studies reporting the predictive value of HRV parameters for AF recurrence or in which HRV parameters in AF recurrence and non-recurrence groups were individually reported. Results: Finally we enrolled 16 studies including 2,352 patients. Higher rMSSD could independently predict AF recurrence following catheter ablation (OR 1.02, 95% CI 1.00–1.04; p = 0.03). Higher HF (OR 1.55, 95% CI 1.05–2.28; p = 0.03) and lower LF/HF (OR 1.12, 95% CI 1.03–1.20; p = 0.004) could independently predict AF recurrence within 1 year. Higher SDNN (OR 1.02, 95% CI: 101–1.02; p = 0.0006) could independently predict AF recurrence among paroxysmal AF patients. Almost all HRV parameters within 3 days after catheter ablation and lnHF, lnLF and rMSSD at 3 months after catheter ablation performed significant difference in AF recurrence and non-recurrence groups. Conclusion: HRV, especially higher rMSSD (within short-term and long-term period), was closely related with recurrent AF following catheter ablation, highlighting the clinical importance of HRV in the prognosis of AF following catheter ablation. Keywords: atrial fibrillation, heart rate variability, recurrence, systematic review, meta-analysis